Adsorption of some heavy metal ions from aqueous solutions on Nafion 117 membrane - Mahmoud El-Sayed Nasef, Mohamed (Elsevier, 2009)
Nafion 117 membrane was investigated for the removal of Ni(II), Co(II), Pb(II), Cu(II) and Ag(I) metal ions from their synthesized aqueous solutions. The different variables affecting the adsorption capacity of the membrane such as contact time, initial metal ion concentration in the feed solution, pH of the sorption medium and temperature of the solution were investigated on a batch sorption basis. The affinity of Nafion 117 membrane towards heavy metal ions was found to increase in the sequence of Cu(II), Ni(II), Co(II), Pb (II), and Ag(I) with adsorption equilibrium achieved after 30 min for all metal ions. Among all parameters, pH has the most significant effect on the adsorption capacity, particularly in the range of 3.1-5.9. The variation of temperature in the range of 25-65 degrees C was found to have no significant effect on the adsorption capacity. Nafion 117 membrane was found to have high stability combined with repeated regeneration ability and can be suggested for effective removal of heavy metal ions such as Cu(II), Ni(II) and Co(II) from aqueous solutions.